Perancangan Sistem Aplikasi Repositori Dokumen Digital sebagai Pendukung Borang IAPS 4.0 Kriteria 7 - Yisti Vita Via; Fetty Tri Anggraeny; Nurfiana (Teknik Komputer Politeknik Negeri Sriwijaya, 2021)
In each funded research activity or publication research, various documents must be produced as evidence of the implementation of the activity. But often these documents are not well organized. Even though these documents are very important for the administrative needs of higher education institutions, one of which is proof of filling in the Study Program Performance Report (LKPS) and Self Evaluation Report (LED) tables in the Study Program Accreditation Instrument (IAPS) 4.0, especially criterion 7, namely research. One way to overcome this problem is to provide a repository for archive management of research documents in digital form. This research designs database systems and business processes in storing and managing digital documents as evidence of research activities and publications. The design of the database system in this application is adapted to the needs of the repository of data on filling in the LKPS table and IAPS 4.0 LED forms related to Criterion 7. Several important points in filling in the table in the LKPS are related to the number of research and publications by lecturers, the number of research funds, publication citations, and even data regarding the output of research grants. The design implementation of this digital archive repository system will later be developed in the form of a user-friendly web-based application to facilitate the management of each research and publication digital document archive. Keywords— Repository Systems, Digital Documents, Database Design, Forms of IAPS 4.0